IMPORTANCE OF VISUAL INFORMATION AND SURFACE SUPPORTON POSTURAL BALANCE CARRIER BY LEPROSY (Fiep Bulletin - online, 2012)
Introduction: Leprosy is a chronic infectious disease and neurological considered to affect the peripheral nervous system and dermatological skin and mucosa. The correlation between abnormal plantar sensitivity and balance disorder occurs by the integration of proprioception and sensory information. Objective: The aim of this study was to analyze the postural control of subjects with sequelae of leprosy through the force platform, and compared with healthy subjects. Methods The sample is composed of 30 patients were subdivided into two groups, control group (CG) and Group Hansen (GH). The data area of body sway were obtained using a force platform in the open and closed eye conditions, and stable and unstable surface. Results: The eyes open and closed conditions affect the way both groups. The different support surfaces affect the group of patients suffering from leprosy only on the condition eyes open. Conclusion: Patients with sequelae of leprosy were not sensitive to different visual conditions, but variations on the support surface show differences in the ability to maintain stability only in the eyes open condition.
Keywords: Leprosy; postural balance; proprioception.